Analysis of the Mural at Duku Station Gate, West Sumatra, Reviewed from the Perspective of Symbolic Interactionism - Syahrul, Syahfilna; -, Suryanti; Rian, Rica (Institut Seni Indonesia Padang Panjang, 2024)
This study “Analyzes the Mural at Duku West Sumatra Station Gate observation by symbolic interactionism”. Held in Padang Pariaman, West Sumatra. This research to find artistic functions (personal, social and physical) and the style (style) of the muralists mural, the way people respond to the meaning in the visual mural and the meaning affects their perception of the social message to be conveyed. The theory used by the analysis the perspective of the community interpreting the mural at the Gate of Duku West Sumatra station, using symbolic interactionism theory assumed that human create mean from process communication. This research will use a type of descriptive approach. Getting resource persons was carried out purposively, then respondents through a qualitative rating scale questionnaire. The process of analyzing interview data, observations, documents, and questionnaires with the Flow Chart Analysis technique by Miles and Huberman. The result of research be found 6 mural at the Station Duku and reaction responde by quetionnaires about mural mentioned. Be based on the result reflects the symbolic interactionism between the community and the mural, which mean the result the community with easier receive the meaning, interpreting social messages, assessing visual appearance, and seeing it as a representation of Minangkabau.